A chip-based multiuser detector for the downlink of a DS-CDMA system using a folded state-transition trellis. - Sim, H.K.
The maximum-likelihood sequence estimation (MLSE) multiuser detector has very good performance but at the expense of high computational complexity. The Viterbi algorithm is employed to implement the MLSE in the asynchronous uplink. In this scheme, the various bit-combinations are taken to be the different states in the decoding trellis. However, the number of states increases exponentially with the number of active users. We propose a scheme that exploits the feature of power-equality in the downlink to reduce the number of states involved. Each transmitted chip value can only take a certain number of possible discrete values. Using these discrete values as the states in the transition trellis diagram and operating the Viterbi algorithm at the chip level, the number of states is reduced from 4K to (K+1) L where K is the number of users and L is the number of paths in the multipath channel
Keywords: DS-CDMA system; MLSE multiuser detector; Viterbi algorithm; Active users; Asynchronous uplink; Bit-combinations.; Chip-based multiuser detector; Computational complexity; Decoding trellis; Downlink; Folded state-transition trellis; Maximum-likelihood sequence estimation multiuser detector; Multipath channel; Performance; Power-equality.; Transition trellis diagram; Transmitted chip value